KAJIAN TEKNIS PENDEDERAN IKAN KERAPU CANTANG (Epinephelus fuscoguttatus >< Epinephelus lanceolatus) SECARA INTENSIF DI BPBAP SITUBONDO: TECHNICAL STUDY FOR INTENSIVE NURSERY OF CANTANG GROUPER (Epinephelus fuscoguttatus >< Epinephelus lanceolatus) AT BPBAP SITUBONDO. - Khumaidi, Ach.; Faizin, Rohmanul; Prakosa, Dimas Galang (Journal of Aquatropica Asia, 2022)
Grouper production in Indonesia can be supported by hybridization technology which can produce grouper species with relatively faster growth and more resistance to disease. Cantang grouper is a type of grouper fish that was engineered by crossbreeding between female tiger grouper (Epinephelus fuscoguttatus) and male grouper Kertang (Epinephelus lanceolatus). The purpose of this study was to determine the stages and technology of nursery grouper Cantang which was carried out at BPBAP Situbondo. The method used in this research is the method of observation, participation, and interviews. The primary data needed in this study are data on infrastructure, data on the number and size of seeds, feed management, water quality management, and harvesting. The data is presented with a descriptive method by discussing the data that has been obtained compared to the theories that have developed at this time. The results of this study indicate that cantang grouper nursery activities start from tank preparation, water filling, seed selection and distribution, feed management, water quality, fish pest and disease control, grading, and harvesting of cantang grouper seeds. During the practice period, the seeds were spread from hatcheries with a stocking density of 3000 to 5000 individuals in one tank with a size of 4 x 2.5 x 1 m, or the equivalent of 300 to 500 individuals/m3. The distribution of seeds is carried out after the acclimatization process, namely the adaptation process before releasing the seeds. After the seeds are removed, the tub is given an antiseptic to prevent disease in the seeds. There are several factors that can affect the growth rate of seeds, namely water quality management and feeding. During the maintenance period, a flowing water system is used, so that the water used is continuously renewed. In the morning, the seeds are flushed and soaked using fresh water, with the aim of releasing mucus on the seeds so as to reduce the potential for disease outbreaks. Nursery grouper at BPBAP Situbondo can run optimally by paying attention to the stages of cultivation, especially in the feed management and water quality management.